Empowering Students with Hidden Disabilities : a Path to Pride and Success. - Izzo, Margo Vreeburg (Brookes Publishing, 2015)
Dare to Dream discusses critical topics for young people with hidden disabilties, such as self-advocating, developing positive relationships with mentors, planning for college, successful working life, interpersonal skills, and satisfying relationships.